Optimal Management of Frontal Fibrosing Alopecia: A Practical Guide - Imhof R; Tolkachjov SN (Dove Medical Press, 2020)
Reese Imhof,1 Stanislav N Tolkachjov2 1Mayo Clinic Alix School of Medicine, Rochester, MN, USA; 2Epiphany Dermatology, Dallas, TX, USACorrespondence: Stanislav N Tolkachjov Email stan.tolkachjov@gmail.comAbstract: Frontal fibrosing alopecia (FFA) is a primary lymphocytic cicatricial alopecia that is often considered a clinical variant of lichen planopilaris (LPP) due to their shared histopathologic features. FFA is characterized by the recession of the frontal, temporal, or frontotemporal hairline; the clinical pattern is distinct and usually includes eyebrow hair loss, as well as other associated symptoms. Pruritus, facial papules, eyelash loss, body hair involvement, and trichodynia may also occur in addition to the frontotemporal recession and eyebrow loss classically seen. Early diagnosis and prompt treatment are critical as FFA is a progressive disorder that can result in permanent hair loss. FFA is challenging as patients may not present or be recognized until the disease has progressed. Additionally, there is currently no consensus or standard treatment regimen for FFA. While many different therapies have been reported as beneficial, there are a limited number of published guidelines for the treatment of FFA. This article is a review of the literature on treatment modalities for FFA and the objective is to offer a practical guide for clinicians on the evidence-based management options currently available in the literature.Keywords: alopecia, frontal fibrosing alopecia, hair loss, scarring alopecia, treatment, management, hair, inflammatory hair disorder, lichen planopilaris, primary lymphocytic cicatricial alopecia, scarring